Analysis of Profitability, Activity, and Interest Rates on Dividend Policy in Non-Cyclical Consumer Sector - Auliarrahman, Hasya Difa; Pinem, Dahlia (Jurnal Multidisiplin Madani, 2024)
Dividend policy is a company's decision regarding whether profits earned will be distributed to investors as dividends or kept as retained earnings to fund future company investments. Factors that influence dividend policy can be internal and external factors of the company. The aim of carrying out this research is to determine the influence of profitability, activity and interest rates on dividend policy in non-cyclical consumer sector companies in Indonesia. The sampling technique used was purposive sampling which was based on criteria, resulting in 26 non-cyclical consumer companies listed on the Indonesia Stock Exchange (IDX) for the 2018-2022 period. The analysis technique used in this research is panel data regression analysis as hypothesis testing with a significance level of 5% (0.05) and uses the help of Eviews 12 software in its processing. Based on the results of data processing, this research shows that profitability has no significant on dividend policy, activity has no significant on dividend policy, and interest rates have a significant negative on dividend policy. The results of this research show that external monetary aspects, namely interest rates, influence dividend policy in the non-cyclical consumer sector more than internal aspects of the company